2023
DOI: 10.3233/shti230061
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Barriers for Interoperability: A Reference Implementation of CSV-FHIR Transformation Using Open-Source Tools

Abstract: FHIR is a widely accepted interoperability standard for exchanging medical data, but data transformation from the primary health information systems into FHIR is usually challenging and requires advanced technical skills and infrastructure. There is a critical need for low-cost solutions, and using Mirth Connect as an open-source tool provides this opportunity. We developed a reference implementation to transform data from CSV (the most common data format) into FHIR resources using Mirth Connect without any ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The usage of Mirth as a transformation engine is an intuitive choice due to its functionality and product scope. So various studies are found dealing with the transformation from HL7 v2 message into further target formats, including structural reformation into JSON [23] or standardization into HL7 FHIR [24]. Our approach is based on a prior study that evaluated the transformation of StructureMaps into Mirth channels [25].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…The usage of Mirth as a transformation engine is an intuitive choice due to its functionality and product scope. So various studies are found dealing with the transformation from HL7 v2 message into further target formats, including structural reformation into JSON [23] or standardization into HL7 FHIR [24]. Our approach is based on a prior study that evaluated the transformation of StructureMaps into Mirth channels [25].…”
Section: Comparison With Prior Workmentioning
confidence: 99%